Implementasi Penggunaan Artificial Intelligence Sebagai Alat Bantu Hukum Di Indonesia Dalam Menuju Society 5.0 - Timotius Dwipangestu; Muhammad Shidqii Amirrul Bari; Bagus Sugara Putra Firlant Irawan; Faiz afzal mulyawan (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
Society 5.0 aims to make things easier by integrating virtual and physical spaces and incorporating artificial intelligence (hereafter referred to as AI). Therefore, the purpose of this research is to utilize AI as legal aid towards Society 5.0 in Indonesia. Artificial intelligence in the legal field helps many legal practitioners in conducting due diligence and investigations that are usually done by lawyers. AI can also analyze legal documents and find weaknesses and flaws in legal documents, usually contracts. This shows the huge potential of artificial intelligence. Therefore, there is nothing wrong with AI being used more widely in this country, becoming a legal tool to solve people's problems.